2004
DOI: 10.1097/01.aog.0000136087.46864.e4
|View full text |Cite
|
Sign up to set email alerts
|

Health, Sociodemographic Data, and Pregnancy Outcome in Women With Antepartum Depressive Symptoms

Abstract: Women depressed during pregnancy constitute a group without an increased risk for adverse obstetric or neonatal outcome but with a high risk for postpartum depressive symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
66
1
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(80 citation statements)
references
References 21 publications
8
66
1
5
Order By: Relevance
“…Defining, measuring and assessing PND PND is variously defined as commencing within 6 weeks (WHO ICD 2007) or 4 weeks of delivery (DSM-IV), and evidence from HICs suggests that the depressive episode might begin during pregnancy (Evans et al, 2001;Larsson et al, 2004). PND can be assessed either clinically or through the use of screening instruments such as the Edinburgh Postnatal Depression Scale (EPDS) (Cox & Holden, 1996;Cox et al, 1987), Beck Depression Inventory (BDI) (Beck et al, 1996), Zung Self-Rating Depression Scale (Zung, 1971), the Kessler Psychological Distress Scale (K10) (Kessler et al, 2002) and the Self-Regulation Questionnaire (SRQ-20) (Harding et al, 1980) among others?…”
Section: Introductionmentioning
confidence: 99%
“…Defining, measuring and assessing PND PND is variously defined as commencing within 6 weeks (WHO ICD 2007) or 4 weeks of delivery (DSM-IV), and evidence from HICs suggests that the depressive episode might begin during pregnancy (Evans et al, 2001;Larsson et al, 2004). PND can be assessed either clinically or through the use of screening instruments such as the Edinburgh Postnatal Depression Scale (EPDS) (Cox & Holden, 1996;Cox et al, 1987), Beck Depression Inventory (BDI) (Beck et al, 1996), Zung Self-Rating Depression Scale (Zung, 1971), the Kessler Psychological Distress Scale (K10) (Kessler et al, 2002) and the Self-Regulation Questionnaire (SRQ-20) (Harding et al, 1980) among others?…”
Section: Introductionmentioning
confidence: 99%
“…3 It has also been reported that newborn infants of anxious women cry significantly more frequently infants of less anxious women [5]. In depressed pregnant women, obstetric complication, shorter gestation, and spontaneous preterm labor are observed more frequently [14,15]. Newborn infants of depressed women have shown poor performance on the Brazelton Neonatal Behavior Assessment Scale and they cried so excessively that they were difficult to soothe [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, there are definite increases in psychiatric morbidity, particularly depression, during pregnancy [Carter et al, 2005;de Tyche et al, 2005;Evans et al, 2001;Fatoye et al, 2004;Marcus et al, 2003;O'Boyle et al, 2005]. Antenatal depression had been identified as a risk factor for PND [Jossefson et al, 2001;Larsson et al, 2004], adverse obstetrical and neonatal outcomes [Chung et al, 2001], and growth retardation in infants [Zukerman et al, 1989]. Because studies have shown that depression is more common late in the pregnancy [Bennet et al, 2004;Kumar and Robson, 1984;Rofe et al, 1993], and most pregnant women in Africa schedule delivery late in the second or the third trimester, assessing for depression in late pregnancy is appropriate for detecting women in need of intervention to safeguard maternal and family psychosocial well-being.…”
Section: Introductionmentioning
confidence: 99%